A three-dimensional elasto-plastic dynamic response procedure for concrete-faced rockfill dams - Bin Xu; Yang Zhou; Jingmao Liu; Xiang Yu (International Journal of Distributed Sensor Networks)
Equivalent linear dynamic analysis is the primary method of analysis for concrete-faced rockfill dams during earthquake. However, this method cannot be directly used to estimate permanent deformation during earthquake, which is important to evaluate the dynamic safety of concrete-faced rockfill dams. To bridge this gap, an elasto-plastic dynamic response procedure based on finite element method is presented to estimate the construction, impoundment, and dynamic characteristics of concrete-faced rockfill dams. This procedure involves a generalized plasticity model for rockfill materials and an ideal elasto-plastic model for interface between concrete face slab and rockfill material. The construction, impounding process, and seismic behavior of a 150-m-tall concrete-faced rockfill dam were simulated using seismic motion based on Chinese code for seismic design of hydraulic structures of hydropower project with the peak ground acceleration of 0.3 g as an excitation to validate the procedure. On the basis of the numerical simulation results of the step-by-step construction, reservoir impoundment and seismic response of a concrete-faced rockfill dam, dam settlement, joint deformation, stress, and deformation of slab were analyzed. The results indicate that the dam settlement and deformation of joint can be directly obtained by the procedure during earthquake. The construction, impoundment, and seismic analysis could be considered in one procedure.